The detection of feline coronaviruses in blood samples from cats by mRNA RT-PCR - Can-Sahna, Kezban; Ataseven, Veysel Soydal; Pinar, Dilek; Oguzoglu, Tuba Cigdem (Sage Publications Ltd, 2007)
In this study, 26 blood samples were collected from 25 healthy cats and one cat with clinical signs suggestive of feline infectious peritonitis (FIP), namely, fever, weight loss, enlarged abdomen, and ascites. Blood samples were tested for feline coronavirus (FCoV) messenger RNA (mRNA) by an reverse transcriptase-polymerase chain reaction (RT-PCR) assay which has previously been described to have a high specificity in the diagnosis of clinical FlP [Simons AF, Vennema H, Rofina JE, Pol JM, Horzinek MC, Rottier PJM,Egberink HF (2005) A mRNA PCR for the diagnosis of feline infectious peritonitis. Journal of Virological Methods 124, 111-116]. Overall we found 14 (54%) of the cats were positive for FCoV including the cat with clinical disease, but the high rate of positivity among healthy cats suggested a poor specificity for the clinical (diagnosis of FlP among these cats. it was observed that the positivity rate was highest in cats aged between 6 months-1year old. Our findings suggest that FCoVs may be present in the blood samples from healthy cats as well as cats with clinical FIR (c) 2007 ESFM and AAFP. Published by Elsevier Ltd. All rights reserved.
Keywords: Infectious Peritonitis; Enteric Coronavirus